(untitled) (International Journal of Medical and Surgical Sciences, 2015)
Mammalian sperm con jugation phenomenon occurs both in the epididymis or post ejaculation. Sperm conjugates consist of tens to hundreds of partner sperm. The combination of sperm is found in the ejaculate of some species but it is unknown if the female tract amount reaching the área of ??fertilization (distal third of the tubes) and if the dissociation before or during interaction with the oocyte cumulus. Various mechanisms have been proposed by which the formation of these structures favor fertilization: a. increased speed of scrolling synergies with individual sperm, particularly in cases of sperm, b competition. conjugated sperm protection against the hostile environment, c. prevention of early acrosome reaction, among others. Our group described this phenomenon in rat and mouse rosettes and proposed calling them a possible associative mechanism. These conjugates consist of groups of sperm joined at their heads and with their free scourges in no less than 10 cells. They were described within the lumen of the region of the cauda epididymis, but not in more proximal sites, suggesting that sperm join together must have matured and made contact with factors of epididymal fluid. To know what the final destination of the spermatic conjugates we studied the presence of male gametes conjugate or in the female genital tract after ejaculation rat. Samples of the contents of the tubes obtained different times allowed us to observe mating post near the complex conjugates cumulus - oocyte. But only individual sperm between the cumulus cells were observed. This suggests that the conjugates after reaching sperm fertilization area are separated into individual sperm.